The Impact of the COVID-19 Pandemic on Neonatal Services: A Review Article: Covid and neonatal services - Alfaifi, Jaber Ahmed (Technium BioChemMed, 2023)
Introduction: The COVID-19 pandemic has significantly impacted healthcare systems worldwide, including neonatal services. The pandemic has disrupted the delivery of neonatal care, leading to challenges in providing essential services to newborns and their families. This review article aims to explore the impact of COVID-19 on neonatal services and identify strategies for mitigating the effects of the pandemic. Methods: A literature search was conducted using PubMed, Embase, and Cochrane Library databases. The search terms used were "COVID-19," "neonatal care," "neonatal services," "prematurity," "low birth weight," and "infant mortality." Articles published between January 2020 and August 2021 were included in this review. Results: The COVID-19 pandemic has reduced the number of antenatal visits, delayed referrals, and decreased access to specialized care for high-risk pregnancies. The pandemic has also disrupted the delivery of essential neonatal care services such as breastfeeding support, kangaroo mother care, and immunization programs. Moreover, there has been an increase in maternal stress and anxiety due to restrictions on visitation policies in neonatal intensive care units (NICUs). These factors have contributed to increased preterm births, low birth weight infants, and infant mortality rates. Conclusion: The COVID-19 pandemic has significantly impacted neonatal services worldwide. Maintaining essential neonatal care services during pandemics is crucial to prevent adverse outcomes for newborns and their families. Healthcare providers must implement strategies to mitigate the effects of the pandemic on neonatal care delivery. These strategies include telemedicine consultations for antenatal visits, home-based follow-up programs for high-risk pregnancies, virtual breastfeeding support groups, and modified visitation policies in NICUs.